Managing extended supply chains. Issue 2 (14th April 2021) - Choi, Thomas Y.; Narayanan, Sriram; Novak, David; Olhager, Jan; Sheu, Jiuh‐Biing; Wiengarten, Frank
Abstract: We address how to manage extended supply chains that lie beyond the first‐tier suppliers. The first‐tier suppliers have their suppliers who provide them with goods or services. While lower‐tier suppliers are often not an explicit concern of the focal firm, the firm's performance not only depends on the performance of its first‐tier suppliers, but also on the performance of their suppliers and beyond. These lower‐tier suppliers are much less visible and may not even be known to the focal firm. Our intention is to bring awareness to the importance of these lower‐tier suppliers and capture possible strategies that buying companies may pursue to manage them. Extended supply chains are complex and involve evolving relationships between various buyers and suppliers that are located along different tiers of the chain and across different parts of the globe. We address several topic areas and suggest emerging research focuses that should be considered in coming years.